Active energy ray-curable coating composition and molded article
By using an active energy ray curing type covering composition containing specific compounds, the chemical resistance, weather resistance and wear resistance of the resin material in severe environments is solved, and efficient adhesion and durability are achieved. .
Patent Information
- Application Number
- CN202380049968.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-12
- Filing Date
- 2023-06-29
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art cannot completely solve the chemical resistance, weather resistance and wear resistance of resin materials in outdoor and harsh environments.
An active energy ray curing type covering composition containing a (meth)acrylate compound having isocyanurate bond, a polyfunctional amino group having isocyanurate bond or ureaforate bond Formate compounds, and compounds containing more than 6 (meth)acryloyl groups in one molecule.
It has achieved high chemical resistance, weather resistance and wear resistance of resin materials, especially in high temperature and high humidity environments, and is suitable for protective coatings of automobiles and building materials.
Smart Images

Figure CN119452046A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an active energy ray-curable coating composition and a molded product. Background Art
[0002] Among resin materials, transparent resin materials represented by polycarbonate and the like are widely used in various applications due to their low specific gravity, light weight, easy processing, and higher impact resistance than inorganic glass.
[0003] On the other hand, resin materials have the following disadvantages: the surface is easily scratched, easily loses gloss or transparency, is easily corroded by organic solvents, has poor weather resistance (e.g., light stability to ultraviolet rays, etc.), poor heat resistance, etc. Therefore, resin materials are often used by being covered with various protective films for the purpose of improving their surface properties.
[0004] Examples of such a protective film include a hard coat layer obtained by curing an active energy ray-curable coating composition.
[0005] Resin materials used outdoors require both abrasion resistance and excellent weather resistance. As active energy ray-curable covering compositions having both abrasion resistance and weather resistance, there are known active energy ray-curable compositions obtained by combining a mono- or polypentaerythritol poly(meth)acrylate compound modified with caprolactone, an isocyanurate ring-containing urethane (meth)acrylate, and poly[(meth)acryloyloxyalkyl]isocyanurate in a specific ratio (see Patent Document 1).
[0006] In addition, Patent Document 2 discloses an ultraviolet curable coating composition which is excellent in transparency, abrasion resistance and weather resistance and is also excellent in warm water resistance, wherein the ultraviolet curable coating composition is obtained by combining a urethane acrylate having 4 to 9 acryloyl groups in the molecule, a urethane acrylate having 1 to 3 acryloyl groups in the molecule and a polyester skeleton in the resin skeleton, a urethane acrylate having 1 to 3 acryloyl groups in the molecule and no polyester skeleton in the resin skeleton, an acetophenone-based photopolymerization initiator, a phosphine oxide-based photopolymerization initiator, an ultraviolet absorber and a light stabilizer in a specific ratio.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2007-314770
[0010] Patent Document 2: Japanese Patent No. 5956401 Summary of the invention
[0011] Problem that the invention aims to solve
[0012] In recent years, resin materials and active energy ray-curable coating compositions that can be used in harsh environments such as outdoors and around cars are required to have not only weather resistance and abrasion resistance, but also resistance to acid rain and car battery fluid, that is, excellent chemical resistance.
[0013] However, in the inventions described in Patent Documents 1 and 2, no research has been conducted on chemical resistance, and the inventions described in Patent Documents 1 and 2 cannot completely solve the problems of chemical resistance, weather resistance, and abrasion resistance.
[0014] The present invention has been made in view of the above problems, and provides an active energy ray-curable coating composition capable of forming a cured film having weather resistance and abrasion resistance and high chemical resistance, and a molded article having the cured film.
[0015] Solutions for solving problems
[0016] The present inventors have conducted intensive studies and have found that the following active energy ray-curable coating composition can solve the above-mentioned problems, thereby completing the present invention.
[0017] The active energy ray-curable coating composition comprises:
[0018] As the component (A), a (meth)acrylate compound having an isocyanurate bond represented by the formula (1) described below,
[0019] A compound having an isocyanurate bond or an allophanate bond and having one or more urethane bonds different from these bonds as the component (B), and
[0020] (C) Component: A compound containing 6 or more (meth)acryloyl groups in one molecule.
[0021] That is, the present invention provides the following inventions.
[0022] (1) An active energy ray-curable coating composition comprising the following components (A) to (C), wherein:
[0023] Contains a compound represented by the following formula (1) as component (A),
[0024] Contains a compound represented by the following formula (2) as component (B),
[0025] (C) Component contains a compound having 6 or more (meth)acryloyl groups in one molecule.
[0026]
[0027] (Where R 1 , R 2 and R 3 Each independently represents an oxyalkylene group or a polyoxyalkylene group, X 1 , X 2 and X 3 Each independently represents CH2=CR 4 -CO-, CH2=CR 4 -CO(O(CH2)5-CO) a1 -, a hydrogen atom or an alkyl group, R 4 Represents a hydrogen atom or a methyl group, multiple R 4 can be the same or different, and a1 is an integer greater than 1. 1 ~X 3 At least 2 of them are CH2=CR 4 -CO- or CH2=CR 4 -CO(O(CH2)5-CO) a1 -. )
[0028]
[0029] (Where R 21 ~R 25 each independently represents a group having a polymerizable group,
[0030] Z 21 ~Z 23 Each independently represents a group represented by the following formula (2z),
[0031] L 21 ~L 22 Each independently represents a divalent linking group,
[0032] n1 to n2 are each independently 0 or 1.)
[0033]
[0034] (Where X 21 represents an alkylene group having 2 to 17 carbon atoms,
[0035] * is the connection key,
[0036] Z 1 represents an oxygen atom or a nitrogen atom, Z 2 represents a hydrogen atom or -C(=O)-. 1 When Z is an oxygen atom, 2 is a hydrogen atom. On the other hand, Z 1 When Z is a nitrogen atom, 2 is -C(=O)-, Z1 The nitrogen atom and Z 2 The -C(=O)- of the amine group is bonded to form a ring.
[0037] Formula (2z) is Z in the above formula (2) 21 When the connecting bond * shown in B1 is connected to R 21 Bonding, the connecting bond shown in B2 and L 21 or R 22 Bonding, the connecting bond shown in B3 and L 22 or R 23 Bonding; Formula (2z) is Z in the aforementioned formula (2) 22 When the connecting key * shown in B1 is connected to L 22 Bonding, the connecting bond shown in B2 and R 24 Bonding, the connecting bond shown in B3 and R 23 Bonding; Formula (2z) is Z in the aforementioned formula (2) 23 When the connecting key * shown in B1 is connected to L 21 Bonding, the connecting bond shown in B2 and R 22 Bonding, the connecting bond shown in B3 and R 25 Bonding. )
[0038] (2) The active energy ray-curable coating composition according to (1) above, wherein the compound represented by the formula (2) is any one of the compounds represented by the following formulas (2-1) to (2-4).
[0039]
[0040] (Where R 26 each independently represents a hydrogen atom or a methyl group,
[0041] R 27 Each independently represents an alkylene group, R A -(O-CO-(CH2)5) n - or R A -(O-(CH2)4) n -,
[0042] R A represents an alkylene group,
[0043] n each independently represents an integer of 1 to 10,
[0044] X 22 Each independently represents an alkylene group having 2 to 17 carbon atoms. 26 , R 27 , X 22 can be the same as or different from each other.)
[0045]
[0046] (Where R 26 , R 27 , X 22 Same as above,
[0047] A1 represents a structure obtained by removing a hydroxyl group from the terminal of any one of alkylene glycol, caprolactone-modified glycol, or polytetramethylene glycol. 26 , R 27 , X 22 , A1 may be the same as or different from each other. )
[0048]
[0049] (Where R 26 , R 27 , X 22 As above, the multiple R 26 , R 27 , X 22 can be the same as or different from each other.)
[0050]
[0051] (Where R 26 , R 27 , X 22 , A1 is the same as above, and the multiple R 26 , R 27 , X 22 can be the same as or different from each other.)
[0052] (3) The active energy ray-curable covering composition according to (1) or (2), wherein, in the total solid content of the components (A) to (C), the content of the component (A) is 1% by mass to 85% by mass, the content of the component (B) is 14% by mass to 98% by mass, and the content of the component (C) is 1% by mass to 20% by mass.
[0053] (4) The active energy ray-curable coating composition according to any one of (1) to (3), wherein the component (C) is a polyfunctional urethane acrylate obtained by reacting a diisocyanate compound or a triisocyanate compound with a compound represented by the following formula (3-1) or (3-2).
[0054]
[0055] (Where R 31 ~R 32 Each independently represents a hydrogen atom or a methyl group, and the multiple R31 , R 32 can be the same as or different from each other.)
[0056] (5) The active energy ray-curable coating composition according to any one of (1) to (4) above, wherein the component (C) is a polyfunctional urethane acrylate obtained by reacting an isocyanate compound represented by the following formula (3-3) or (3-4) with a compound represented by the above formula (3-1) or (3-2).
[0057]
[0058] (Where X 31 ~X 32 Each independently represents an alkylene group having 2 to 17 carbon atoms, and R 33 Indicates -R C -O-CO-CH=CH2 or a structure obtained by removing a hydroxyl group from a compound represented by the above formula (3-1) or (3-2), R C represents an alkylene group. 31 , X 32 can be the same as or different from each other.)
[0059] (6) The active energy ray-curable coating composition according to any one of (2) to (5), wherein the component (B) comprises a component (B-1) and a component (B-2),
[0060] The component (B-1) comprises: R in the formula (2-1) or (2-3) 27 At least one of the A -(O-CO-(CH2)5) n - or R A -(O-(CH2)4) n -, or A1 in the above formula (2-2) or (2-4) is a compound having a structure obtained by removing a hydroxyl group from a terminal of polytetramethylene glycol or polycaprolactone diol,
[0061] The component (B-2) comprises: R in the formula (2-1) or (2-3) 27 A compound which is an alkylene group, or a compound in which A1 in the above formula (2-2) or (2-4) has a structure obtained by removing a hydroxyl group from the terminal of an alkylene glycol,
[0062] In the total solid content of the components (A) to (C), the content of the component (B-1) is 9% by mass or more and 90% by mass or less, and the content of the component (B-2) is 5% by mass or more and 60% by mass or less.
[0063] (7) A molded article comprising a cured film of the active energy ray-curable covering composition according to any one of (1) to (6) above and a substrate.
[0064] (8) The molded article according to (7), wherein the substrate is a polycarbonate resin.
[0065] (9) A molded article obtained by bending the molded article according to (7) or (8) above by heat bending.
[0066] (10) The molded article according to any one of (7) to (9) above, which is used for automobile headlamp lenses, automobile glazing, automobile body exterior, plastics for building materials, and steel sheets for building materials.
[0067] Effects of the Invention
[0068] The active energy ray-curable coating composition of the present invention can form a cured coating having excellent chemical resistance, high weather resistance and abrasion resistance. The cured coating has excellent adhesion to resin materials such as polycarbonate and also has excellent adhesion under high temperature and high humidity environments. Therefore, the active energy ray-curable coating composition of the present invention can be suitably used as a hard coating of resin materials in automotive applications and building material applications. DETAILED DESCRIPTION
[0069] <Active energy ray-curable coating composition>
[0070] The active energy ray-curable coating composition of the present invention (hereinafter, sometimes simply referred to as “coating composition” or “composition”) contains components (A) to (C).
[0071] In this specification, the compound represented by formula (1) is referred to as "compound (1)", and the same applies to compounds represented by other formulae. In addition, "acrylate" and "methacrylate" are collectively referred to as "(meth)acrylate". "Acrylic acid" and "methacrylic acid", "acryloyl" and "methacryloyl", "acryloyloxy" and "methacryloyloxy" are also described using "(meth)" as a concept that includes both.
[0072] [(A) ingredient]
[0073] The component (A) is a compound represented by the following formula (1). When the coating composition contains the component (A), the wear resistance and adhesion of the cured film are improved.
[0074]
[0075] In formula (1), R 1, R 2 and R 3 Each is independently an oxyalkylene group or a polyoxyalkylene group.
[0076] The carbon number of the oxyalkylene group is preferably 1-8, more preferably 1-5, particularly preferably 1-3.
[0077] The number of carbon atoms in the polyoxyalkylene group is preferably 1 to 8 per repeating unit, more preferably 1 to 5, and particularly preferably 1 to 3. The number of repeating oxyalkylene groups in the polyoxyalkylene group is preferably in the range of 1 to 10.
[0078] It should be noted that the oxygen atom of the oxyalkylene group and the terminal oxygen atom in the polyoxyalkylene group are 1 , X 2 or X 3 Bonding.
[0079] X 1 , X 2 and X 3 Each independently represents CH2=CR 4 -CO-, CH2=CR 4 -CO(O(CH2)5-CO) a1 -, a hydrogen atom or an alkyl group, but X 1 ~X 3 At least 2 of them are CH2=CR 4 -CO- or CH2=CR 4 -CO(O(CH2)5-CO) a1 - That is, the compound (1) is a difunctional or trifunctional (meth)acrylate.
[0080] R 4 Represents a hydrogen atom or a methyl group, multiple R 4 They may be the same or different, and are preferably hydrogen atoms.
[0081] a1 is an integer of 1 or more, preferably an integer of 1 to 3, more preferably 1 or 2, and particularly preferably 1.
[0082] Among them, X 1 , X 2 and X 3 Preferably CH2=CR 4 -CO-, CH2=CR 4 -CO(O(CH2)5-CO) a1 - or a hydrogen atom, more preferably X 1 ~X 3 At least two of them are CH2=CR 4 -CO-, particularly preferably all three are CH2=CR 4 -CO-.
[0083] Particularly preferred examples of the compound (1) include compounds represented by the following formula (1-1).
[0084] In the following formula, R 4 Same as above, R 1 '~R 3 ' is an alkylene group having 1 to 5 (preferably 1 to 3) carbon atoms.
[0085]
[0086] Specific structures of the component (A) include bis(2-acryloyloxyethyl)hydroxyethyl isocyanurate, tris(2-acryloyloxyethyl)isocyanurate (trade names Aronix M-313 and Aronix M-315 manufactured by Toagosei Co., Ltd., trade names NK Ester A9300 and A9300S manufactured by Shin-Nakamura Chemical Co., Ltd., and SR368 and SR368NS manufactured by Arkema), bis(2-acryloyloxypropyl)hydroxyethyl isocyanurate, tris(2-acryloyloxypropyl)isocyanurate, tris(2-acryloyloxyethyl)isocyanurate modified with one caprolactone per molecule (trade name Aronix M-325 manufactured by Toagosei Co., Ltd.), and tris(2-acryloyloxyethyl)isocyanurate modified with three caprolactones per molecule (trade name Aronix M-327 manufactured by Toagosei Co., Ltd.).
[0087] (A) The component may be used alone or in combination of two or more.
[0088] In 100% by mass of the total solid content of components (A) to (C), the content of component (A) is preferably 1 to 85% by mass, more preferably 2.5 to 70% by mass, further preferably 5 to 50% by mass, and particularly preferably 8 to 20% by mass. By setting the above lower limit or more, abrasion resistance and adhesion are further improved, and by setting the above upper limit or less, weather resistance and chemical resistance are further improved.
[0089] [(B) ingredient]
[0090] The component (B) is a compound represented by the formula (2). When the coating composition contains the component (B), the weather resistance and adhesion of the cured film are improved.
[0091]
[0092] In formula (2), R 21 ~R 25 Each independently is a group having a polymerizable group.
[0093] As R 21 ~R 25 The polymerizable group is preferably a (meth)acryloyl group (CH2=CR 4 -CO-(R 4 Same as above)), R 21 ~R 25 A combination of a (meth)acryloyl group and a divalent linking group is preferred.
[0094] As R 21 ~R 25 The divalent linking group may include an alkylene group having 1 to 30 carbon atoms and optionally having a substituent, an oxyalkylene group having 1 to 30 carbon atoms and optionally having a substituent, -O-, -C(=O)-O-, -OC(=O)-, -C(=O)-, -OC(=O)-O-, -C(=O)-NH-, -NH-C(=O)-, -OC(=O)-NH-, -NH-C(=O)-O-, -NH-, -C(=NH)-NH- and -NH-C(=NH)-, and combinations thereof. It should be noted that the hydrogen atoms of the groups listed as the divalent linking groups may be substituted by alkyl, alkoxy, acyl, and the like.
[0095] n1 to n2 are each independently 0 or 1.
[0096] L 21 ~L 22 Each is independently a divalent linking group.
[0097] L 21 ~L 22 The divalent linking group preferably has a structure obtained by removing hydroxyl groups from both ends of alkylene glycol, caprolactone-modified diol, or polytetramethylene glycol. The alkylene glycol is preferably an alkylene glycol having 2 to 10 carbon atoms, and the number of repeating tetramethylene groups in polytetramethylene glycol is preferably 8 to 30.
[0098] Examples of the caprolactone-modified diol include "PLACCEL 205", a polycaprolactone diol having a mass average molecular weight of 530; "PLACCEL 205BA", a polycaprolactone diol having a mass average molecular weight of 530 and having a carboxyl group in a side chain; "PLACCEL L205AL", a polycaprolactone diol having a mass average molecular weight of 500 which is liquid at room temperature; "PLACCEL 205H", a polycaprolactone diol having a mass average molecular weight of 530 and having improved water resistance compared to PLACCEL 205; "PLACCEL 205U", a polycaprolactone diol having a mass average molecular weight of 530 and having a lower viscosity and acid value than PLACCEL 205; and "PLACCEL L205AL", a polycaprolactone diol having a mass average molecular weight of 830. 208", "PLACCELL208AL", a polycaprolactone diol with a mass average molecular weight of 830 which is liquid at room temperature, "PLACCEL 210", a polycaprolactone diol with a mass average molecular weight of 1000, "PLACCEL 210BA", a polycaprolactone diol with a mass average molecular weight of 1000 having a carboxyl group in the side chain, "PLACCEL 210CP", a polycaprolactone diol with a mass average molecular weight of 1000 having a lower acid value and improved water resistance than PLACCEL 210, "PLACCEL 210N", a polycaprolactone diol with a mass average molecular weight of 1000 having a narrower molecular weight distribution than PLACCEL 210, "PLACCEL 212", a polycaprolactone diol with a mass average molecular weight of 1250, "PLACCEL 213", a polycaprolactone diol with a mass average molecular weight of 1250 which is liquid at room temperature, L212AL", "PLACCEL 220", a polycaprolactone diol with a mass average molecular weight of 2000, "PLACCEL 220BA", a polycaprolactone diol with a mass average molecular weight of 2000 having a carboxyl group in the side chain, "PLACCEL 220CPB", a polycaprolactone diol with a mass average molecular weight of 2000 having a lower acid value and improved water resistance than PLACCEL 220, "PLACCEL 220N", a polycaprolactone diol with a mass average molecular weight of 2000 having a narrower molecular weight distribution than PLACCEL 220, "PLACCEL 220NP1", a polycaprolactone diol with a mass average molecular weight of 2000 having lower crystallinity than PLACCEL 220, and "PLACCEL 220CPB", a polycaprolactone diol with a mass average molecular weight of 2000 having a lower crystallinity than PLACCEL 220. L220AL", polycaprolactone diol with a mass average molecular weight of 3000, namely "PLACCEL 230", polycaprolactone diol with a mass average molecular weight of 3000 that is liquid at room temperature, namely "PLACCELL 230AL", polycaprolactone diol with a mass average molecular weight of 3000 that has a lower acid value and improved water resistance than PLACCEL 230, namely "PLACCEL"PLACCEL 230CP", "PLACCEL 240", a polycaprolactone diol having a mass average molecular weight of 4000, "PLACCEL 240CP", a polycaprolactone diol having a mass average molecular weight of 4000 having a lower acid value and improved water resistance than PLACCEL 240, "PLACCEL 220EB", a polycaprolactone diol having a mass average molecular weight of 2000 having improved hydrolysis resistance than PLACCEL 220, and "PLACCEL 220EC", a polycaprolactone diol having excellent elastic recovery than PLACCEL 220EB and a mass average molecular weight of 2000 (all trade names, manufactured by Daicel Corporation), etc.
[0099] Among them, from the viewpoint of weather resistance and abrasion resistance of the obtained cured film, polycaprolactone diol having a mass average molecular weight within a range of 500 to 1500 is preferred, and polycaprolactone diol having a mass average molecular weight within a range of 500 to 1000 is more preferred.
[0100] Furthermore, L 21 ~L 22 It is preferred that any of the structures obtained by removing a hydroxyl group from the terminal of any of alkylene glycol, caprolactone-modified glycol or polytetramethylene glycol further have another connecting group. As the other connecting group, it is preferred that "R 21 ~R 25 The groups listed as "divalent connecting group possessed by the
[0101] Z 21 ~Z 23 Each independently has a structure represented by the following formula (2z).
[0102]
[0103] In formula (2z), X 21 The alkylene group is an alkylene group having 2 to 17 carbon atoms, more preferably an alkylene group having 2 to 10 carbon atoms, and still more preferably an alkylene group having 2 to 6 carbon atoms.
[0104] The * shown in formula (2z) is a connecting bond, and formula (2z) is Z in the above formula (2) 21 When the connecting bond * shown in B1 is connected to R 21 Direct bonding, the connecting bond shown in B2 is connected to L 21 or R 22 Direct bonding, the connecting bond shown in B3 and L 22 or R 23 Direct bonding; Formula (2z) is Z in the above formula (2) 22 When the connecting key * shown in B1 is connected to L 22 Direct bonding, the connecting bond shown in B2 is connected to R 24Direct bonding, the connecting bond shown in B3 and R 23 Direct bonding; Formula (2z) is Z in the above formula (2) 23 When the connecting key * shown in B1 is connected to L 21 Direct bonding, the connecting bond shown in B2 is connected to R 22 Direct bonding, the connecting bond shown in B3 and R 25 Direct bonding.
[0105] Z 1 is an oxygen atom or a nitrogen atom, Z 2 is a hydrogen atom or -C(=O)-. 1 When Z is an oxygen atom (-O-), 2 is a hydrogen atom (-H). 1 When Z is a nitrogen atom, 2 is -C(=O)-, Z 1 The nitrogen atom and Z 2 The -C(=O)- of Z forms a ring. 1 When Z is an oxygen atom, the formula (2z) is a structure having an allophanate bond, 1 When it is a nitrogen atom, the formula (2z) is a structure having an isocyanurate bond.
[0106] Among them, the compound (2) is preferably a compound represented by the following formulas (2-1) to (2-4).
[0107]
[0108]
[0109] In formulas (2-1) to (2-4), R 26 Each is independently a hydrogen atom or a methyl group.
[0110] In formulas (2-1) to (2-4), R 27 are each independently an alkylene group having 2 to 10 carbon atoms (preferably 2 to 4 carbon atoms), R A -(O-CO-(CH2)5) n - or R A -(O-(CH2)4) n -.
[0111] R A represents an alkylene group, and is preferably an alkylene group having 2 to 4 carbon atoms.
[0112] n each independently represents an integer of 1-10, and is preferably an integer of 1-5.
[0113] In formulas (2-1) to (2-4), X 22Each independently is an alkylene group having 2 to 17 carbon atoms, preferably an alkylene group having 2 to 10 carbon atoms, and more preferably an alkylene group having 2 to 6 carbon atoms.
[0114] In formula (2-2) and (2-4), A1 is a structure obtained by removing a hydroxyl group from the terminal of any one of alkylene glycol, caprolactone-modified diol, or polytetramethylene glycol, and is 21 ~L 22 The same as described in the description.
[0115] The multiple R in formulas (2-1) to (2-4) 26 , R 27 , X 22 May be the same as or different from each other.
[0116] The component (B) may be used alone or in combination of two or more. Of these, it is preferred to use two or more components (B) in combination from the viewpoint of achieving a good balance of various properties.
[0117] When two or more components are used, the component (B) preferably includes a component (B-1) and a component (B-2). Examples of the component (B-1) include: R in the formula (2-1) or (2-3): 27 At least one of the A -(O-CO-(CH2)5) n - or R A -(O-(CH2)4) n -, or a compound in which A1 in formula (2-2) or formula (2-4) has a structure obtained by removing a hydroxyl group from the terminal of polytetramethylene glycol or polycaprolactone diol. As component (B-2), R of formula (2-1) or formula (2-3) can be listed. 27 A compound which is an alkylene group, or a compound in which A1 in the formula (2-2) or (2-4) has a structure obtained by removing a hydroxyl group from the terminal of an alkylene glycol.
[0118] Among them, preferred is a combination of the component (B-1) represented by formula (2-1) and the component (B-2) represented by formula (2-1) or (2-3), or a combination of the component (B-1) represented by formula (2-2) in which A1 has a polycaprolactone structure and the component (B-2) represented by formula (2-1) or (2-3).
[0119] When the (B) component includes the (B-1) component and the (B-2) component, the content of the (B-1) component is preferably 9 to 90% by mass, more preferably 20 to 70% by mass, further preferably 30 to 60% by mass, and particularly preferably 45 to 60% by mass in 100% by mass of the total solid content of the (A) to (C) components. In addition, the content of the (B-2) component is preferably 5 to 60% by mass, more preferably 10 to 50% by mass, further preferably 15 to 40% by mass, and particularly preferably 20 to 30% by mass in 100% by mass of the total solid content of the (A) to (C) components.
[0120] In 100% by mass of the total solid content of the components (A) to (C), the content of the entire component (B) is preferably 14 to 98% by mass, more preferably 30 to 95% by mass, further preferably 45 to 93% by mass, particularly preferably 60 to 90% by mass, and most preferably 70 to 85% by mass. When the content is set to be above the lower limit, weather resistance is improved, and when the content is set to be below the upper limit, wear resistance is improved.
[0121] [(C) ingredient]
[0122] The component (C) is a compound containing 6 or more (meth)acryloyl groups in one molecule. When the coating composition contains the component (C), the abrasion resistance and chemical resistance of the cured film are improved.
[0123] The component (C) is not particularly limited as long as it has 6 or more (meth)acryloyl groups in one molecule, and examples thereof include multifunctional (meth)acrylates such as dipentaerythritol hexa(meth)acrylate, tripentaerythritol hepta(meth)acrylate, tripentaerythritol octa(meth)acrylate, and polypentaerythritol poly(meth)acrylate; and urethane (meth)acrylates obtained by reacting an isocyanate compound with a (meth)acrylate compound.
[0124] The polyfunctional (meth)acrylate as the component (C) is preferably a compound represented by the following formula (3-0).
[0125]
[0126] In formula (3-0), multiple R 30 At least 6 of them represent CH2=CR B -COO-, remaining R 30 Represents hydroxyl or CH2=CR B -COO-.
[0127] R B represents a hydrogen atom or a methyl group, R B When it is a hydrogen atom, the polymerizable unsaturated group is an acryloyl group, and R BWhen it is a methyl group, the polymerizable unsaturated group is a methacryloyl group.
[0128] That is, compound (3-0) is a polymerizable compound having a pentaerythritol skeleton and having 6 or more (meth)acryloyloxy groups as polymerizable unsaturated groups in the structure. By having 3 or more polymerizable unsaturated groups, the crosslinking density during curing becomes higher, resulting in improved wear resistance and chemical resistance.
[0129] n30 represents an integer of 1 to 4, preferably an integer of 1 to 3, more preferably 1 or 2, and particularly preferably n30=1 and compound (3-0) has a dipentaerythritol skeleton.
[0130] The compound (3-0) may be used alone or in combination of two or more.
[0131] (C) Urethane (meth)acrylate as the component can be obtained by reacting a (meth)acrylate compound having a hydroxyl group with an isocyanate compound.
[0132] As the (meth)acrylate compound having a hydroxyl group used for the production of the urethane (meth)acrylate, a compound represented by the following formula (3-1) or (3-2) is preferred.
[0133] In the following formula, R 31 ~R 32 Each independently represents a hydrogen atom or a methyl group, and the multiple R 31 , R 32 May be the same as or different from each other.
[0134]
[0135] Furthermore, as the isocyanate compound used for the production of the urethane (meth)acrylate, an aliphatic polyisocyanate or an alicyclic polyisocyanate having two or more isocyanate groups is preferred.
[0136] Specifically, examples include aliphatic polyisocyanates such as 1,4-butane diisocyanate, 1,5-pentane diisocyanate, 1,6-hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, and lysine triisocyanate, or dimers or trimers thereof; and alicyclic polyisocyanates such as norbornane diisocyanate, isophorone diisocyanate, methylenebis(4-cyclohexyl isocyanate), 1,3-bis(isocyanatomethyl)cyclohexane, hydrogenated xylylene diisocyanate, 2-methyl-1,3-diisocyanatocyclohexane, and 2-methyl-1,5-diisocyanatocyclohexane, or dimers or trimers thereof.
[0137] Among them, as the isocyanate compound, a triisocyanate compound represented by the following formula (3-3) or a diisocyanate compound represented by the following formula (3-4) is particularly preferred.
[0138]
[0139] Where, X 31 ~X 32 Each independently represents an alkylene group having 2 to 17 carbon atoms, preferably an alkylene group having 2 to 6 carbon atoms. 31 , X 32 May be the same as or different from each other.
[0140] R 33 Indicates -R C -O-CO-CH=CH2 or a structure obtained by removing a hydroxyl group from a compound represented by the above formula (3-1) or (3-2), R C The alkylene group preferably has 1 to 30 carbon atoms, more preferably 1 to 20 carbon atoms, and particularly preferably 1 to 10 carbon atoms.
[0141] In 100% by mass of the total solid content of components (A) to (C), the content of component (C) as a whole is preferably 1.0 to 20% by mass, more preferably 2.5 to 17.5% by mass, further preferably 5.0 to 15% by mass, and particularly preferably 5.5 to 13% by mass. By setting the above lower limit or more, chemical resistance is improved, and by setting the above upper limit or less, weather resistance is improved.
[0142] [Other ingredients]
[0143] The composition of the present invention may contain other components in addition to the above-mentioned (A) to (C) components within a range in which the effects of the present invention are obtained.
[0144] Other components include, for example, reactive compounds, organic solvents, various resins, fillers, polymerization initiators, stabilizers, ultraviolet absorbers, and leveling agents. In addition, inorganic pigments, organic pigments, extender pigments, clay minerals, waxes, catalysts, surfactants, flow regulators, coupling agents, dyes, rheology control agents, antioxidants, plasticizers, and the like may also be included.
[0145] As the reactive compound, a (meth)acrylate compound other than the components (A) to (C) and a compound having a double bond such as a vinyl group may be mixed. As the (meth)acryloyl compound, monofunctional (meth)acrylates and difunctional to pentafunctional (meth)acrylates which do not correspond to the components (A) to (C) may be mentioned.
[0146] Examples of the monofunctional (meth)acrylate include: (meth)acrylic acid alkyl esters having an alkyl group having 1 to 22 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and lauryl (meth)acrylate; (meth)acrylic acid cycloalkyl esters, such as cyclohexyl (meth)acrylate and isobornyl (meth)acrylate; (meth)acrylic acid ω-alkoxyalkyl esters, such as 2-methoxyethyl (meth)acrylate and 4-methoxybutyl (meth)acrylate;
[0147] Hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, caprolactone-modified hydroxy (meth)acrylate (for example, trade name "PLACCEL" manufactured by Daicel Corporation), polycarbonate-modified hydroxy (meth)acrylate, mono (meth)acrylate of polyester diol obtained from phthalic acid and propylene glycol, mono (meth)acrylate of polyester diol obtained from succinic acid and propylene glycol, polyethylene glycol mono (meth)acrylate, polypropylene glycol mono (meth)acrylate, 2-hydroxy-3- (meth)acryloyloxypropyl (meth)acrylate, (meth)acrylic acid adducts of various epoxy esters, and the like.
[0148] Examples of the di- to penta-functional (meth)acrylates include:
[0149] Di(meth)acrylates of diols such as 1,4-butanediol di(meth)acrylate, 3-methyl-1,5-pentanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 2-methyl-1,8-octanediol di(meth)acrylate, 2-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, and tripropylene glycol di(meth)acrylate;
[0150] Polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, di(meth)acrylate of tri(2-hydroxyethyl)isocyanurate, di(meth)acrylate of diol obtained by adding 4 or more ethylene oxide or propylene oxide to 1 mol of neopentyl glycol, di(meth)acrylate of diol obtained by adding 2 or more ethylene oxide or propylene oxide to 1 mol of bisphenol A, di(meth)acrylate of a glycol obtained by reacting 1 mol of tri(2-hydroxyethyl)isocyanurate with 2 to 3 mols of acrylic acid, trimethylolpropane tri(meth)acrylate, polyethylene glycol di(meth)acrylate modified with ethylene oxide, polypropylene glycol di(meth)acrylate modified with propylene oxide, polytetramethylene glycol di(meth)acrylate modified with tetrahydrofuran, polyisocyanuric acid modified with 1 mol of tri(2-hydroxyethyl)isocyanurate, polyisocyanuric acid modified with 2 to 3 mols of acrylic acid, Ethane-modified glycerol tri(meth)acrylate, propylene oxide-modified glycerol tri(meth)acrylate, di(trimethylol)propane tetra(meth)acrylate, hydroxypivalic acid-modified trimethylolpropane tri(meth)acrylate, ethylene oxide-modified trimethylolpropane tri(meth)acrylate, propylene oxide-modified trimethylolpropane tri(meth)acrylate, ethylene oxide-modified trimethylolpropane tri(meth)acrylate, ethylene oxide-modified phosphoric acid tri(meth)acrylate, ethylene oxide-modified pentaerythritol tetra(meth)acrylate The invention also includes the following: polyol (meth)acrylate, pentaerythritol tetra(meth)acrylate modified with propylene oxide, pentaerythritol tetra(meth)acrylate modified with tetrahydrofuran, polyester (meth)acrylate compounds synthesized by condensation reaction of polyols with (meth)acrylic acid and polyfunctional carboxylic acids, epoxy (meth)acrylate compounds synthesized by addition reaction of novolac type epoxy resins, glycidyl group-containing acrylic polymers and (meth)acrylic acid, acrylic acrylate compounds, and the like.
[0151] The reactive compound may be used alone or in combination of two or more thereof. The amount of the reactive compound used is preferably 0 to 300% by mass relative to 100% by mass of the total solid content of the components (A) to (C).
[0152] Examples of the organic solvent include ester solvents, ketone solvents, ether solvents, aliphatic solvents, aromatic solvents, and alcohol solvents.
[0153] Specifically, as the ester solvent, ethyl acetate, propyl acetate, and butyl acetate can be exemplified; as the ketone solvent, acetone, 2-butanone, methyl ethyl ketone, methyl isobutyl ketone, etc. can be exemplified; as the ether solvent, tetrahydrofuran, dioxolane, etc. can be exemplified; as the aliphatic solvent, hexane, cyclohexane, etc. can be exemplified; as the aromatic solvent, toluene, xylene, etc. can be exemplified; as the alcohol solvent, ethanol, methanol, propanol, butanol, propylene glycol monomethyl ether, etc. can be exemplified.
[0154] In addition, the composition of the present invention can also be a solvent-free composition containing no organic solvent or a high-solid composition having a relatively low content of organic solvent. By setting it to be solvent-free or low solvent / high solid content, it is possible to reduce the environmental load by reducing the amount of volatile organic compounds (VOC). The high-solid composition here refers to, for example, a composition having an organic solvent content of 30% by mass or less in the total amount of the composition.
[0155] In addition, liquid organic polymers may be used to adjust the viscosity. Liquid organic polymers are those that do not directly contribute to the curing reaction, and examples thereof include: modified carboxyl-containing polymers (FLOWLEN G-900, NC-500: Kyoeisha Chemical Co., Ltd.), acrylic polymers (FLOWLEN WK-20: Kyoeisha Chemical Co., Ltd.), amine salts of special modified phosphate esters (HIPLAAD ED-251: Kusumoto Chemicals Co., Ltd.), and modified acrylic block copolymers (DISPERBYK2000; BYK-Chemie).
[0156] As various resins, thermosetting resins or thermoplastic resins can be used.
[0157] Thermosetting resin refers to a resin having a property of being substantially insoluble and infusible when cured by means of heating, radiation or a catalyst. Specific examples thereof include phenolic resin, urea-formaldehyde resin, melamine resin, benzoguanamine resin, alkyd resin, unsaturated polyester resin, vinyl ester resin, diallyl terephthalate resin, epoxy resin, silicone resin, urethane resin, furan resin, ketone resin, xylene resin, thermosetting polyimide resin, benzoxazine resin, active ester resin, aniline resin, cyanate resin, styrene-maleic anhydride (SMA) resin, etc. These thermosetting resins can be used alone or in combination of two or more.
[0158] Thermoplastic resin refers to a resin that can be melt-molded by heating. Specific examples thereof include polyethylene resin, polypropylene resin, polystyrene resin, rubber-modified polystyrene resin, acrylonitrile-butadiene-styrene (ABS) resin, acrylonitrile-styrene (AS) resin, polymethyl methacrylate resin, acrylic resin, polyvinyl chloride resin, polyvinylidene chloride resin, polyethylene terephthalate resin, ethylene vinyl alcohol resin, cellulose acetate resin, ionomer resin, polyacrylonitrile resin, polyamide resin, polyacetal resin, polybutylene terephthalate resin, polylactic acid resin, polyphenylene ether resin, modified polyphenylene ether resin, polycarbonate resin, polysulfone resin, polyphenylene sulfide resin, polyetherimide resin, polyethersulfone resin, polyarylate resin, thermoplastic polyimide resin, polyamideimide resin, polyetheretherketone resin, polyketone resin, liquid crystal polyester resin, fluororesin, syndiotactic polystyrene resin, cyclic polyolefin resin, etc. These thermoplastic resins may be used alone or in combination of two or more.
[0159] As a filler, for example, silica may be blended for the purpose of improving abrasion resistance.
[0160] As silicon dioxide, there is no limitation, and known silicon dioxide particles such as powdered silicon dioxide, colloidal silicon dioxide, and nano silicon dioxide can be used. As commercially available powdered silicon dioxide particles, for example, AEROSIL 50 and 200 manufactured by NIPPONAEROSIL CO., LTD., Sildex H31, H32, H51, H52, H121, and H122 manufactured by Asahi Glass Co., Ltd., E220A and E220 manufactured by Nippon Silica Industries Co., Ltd., SYLYSIA 470 manufactured by Fuji Silysia Chemical Ltd., and SG FLAKE manufactured by Nippon Sheet Glass Co., Ltd. can be cited.
[0161] In addition, commercially available colloidal silica includes, for example, methanol silica sol manufactured by Nissan Chemical Co., Ltd., IPA-ST, MEK-ST, PGM-ST, NBA-ST, XBA-ST, DMAC-ST, ST-UP, ST-OUP, ST-20, ST-40, ST-C, ST-N, ST-O, ST-50, ST-OL, etc.
[0162] Reactive silica can also be used as silica. As reactive silica, for example, reactive compound-modified silica can be cited. As reactive compounds, for example, reactive silane coupling agents having a hydrophobic group, compounds having a (meth)acryloyl group, compounds having a maleimide group, and compounds having a glycidyl group can be cited.
[0163] Examples of commercially available powdered silica modified with a compound having a (meth)acryloyl group include AEROSIL RM50 and R711 manufactured by NIPPON AEROSIL CO., LTD., and examples of commercially available colloidal silica modified with a compound having a (meth)acryloyl group include MIBK-SD, MIBK-SD-L, MIBK-AC-2140Z, and MEK-AC-2140Z manufactured by Nissan Chemical Industries, Ltd. In addition, examples of reactive silica include silica modified with a glycidyl group such as 3-glycidyloxypropyltrimethoxysilane and then subjected to an addition reaction with acrylic acid, and silica modified with a substance obtained by subjecting 3-isocyanatepropyltriethoxysilane to a urethanization reaction with a compound having a hydroxyl group and a (meth)acryloyl group.
[0164] The shape of the silica particles is not particularly limited, and spherical, hollow, porous, rod-shaped, plate-shaped, fibrous or amorphous silica particles can be used. For example, SiliNax manufactured by Nippon Iron & Steel Co., Ltd. can be used as commercially available hollow silica particles.
[0165] The primary particle size is preferably in the range of 5 to 200 nm. If it is 5 nm or more, the inorganic fine particles in the composition can be sufficiently dispersed, and if it is 200 nm or less, sufficient strength of the cured product can be maintained.
[0166] The content of silica in 100% by mass of the composition is preferably 3 to 60% by mass.
[0167] Examples of fillers other than silica include inorganic fillers and organic fillers. The shape of the filler is not limited, and examples thereof include particle-shaped, plate-shaped, and fibrous fillers.
[0168] Fillers with excellent heat resistance include alumina, magnesia, titanium dioxide, zirconium oxide, etc.; fillers with excellent thermal conductivity include boron nitride, aluminum nitride, aluminum oxide, titanium oxide, magnesium oxide, zinc oxide, silicon oxide, etc.; fillers with excellent electrical conductivity include metal fillers and / or metal-coated fillers using metal monomers or alloys (such as iron, copper, magnesium, aluminum, gold, silver, platinum, zinc, manganese, stainless steel, etc.); fillers with excellent barrier properties include minerals such as mica, clay, kaolin, talc, zeolite, wollastonite, montmorillonite, etc., potassium titanate, magnesium sulfate, sepiolite, Hard ascites, aluminum borate, calcium carbonate, titanium oxide, barium sulfate, zinc oxide, magnesium hydroxide; fillers with high refractive index are barium titanate, zirconium oxide, titanium oxide, etc.; fillers showing photocatalytic properties are photocatalytic metals such as titanium, cerium, zinc, copper, aluminum, tin, indium, phosphorus, carbon, sulfur, ruthenium, nickel, iron, cobalt, silver, molybdenum, strontium, chromium, barium, lead, etc., complexes of the aforementioned metals and their oxides, etc.; fillers with excellent wear resistance are metals such as aluminum oxide, zirconium oxide, magnesium oxide, etc., their complexes and oxides, etc.; fillers with excellent conductivity are metals such as silver, copper, tin oxide, indium oxide, etc.; fillers with excellent ultraviolet shielding properties are titanium oxide, zinc oxide, etc.
[0169] These inorganic fine particles can be selected as appropriate according to the application, and can be used alone or in combination. In addition, the above-mentioned inorganic fine particles have various properties in addition to the properties exemplified, so they can be selected as appropriate according to the application.
[0170] In addition to inorganic fibers such as carbon fiber, glass fiber, boron fiber, alumina fiber, SiC (silicon carbide) fiber, inorganic fibers such as activated carbon fiber, graphite fiber, tungsten carbide fiber, ceramic fiber, natural fiber, mineral fibers such as basalt, boron nitride fiber, boron carbide fiber, and metal fiber can also be listed. Examples of the above-mentioned metal fibers include aluminum fiber, copper fiber, brass fiber, stainless steel fiber, and steel fiber.
[0171] Examples of organic fibers include synthetic fibers made of resin materials such as polybenzazole, aromatic polyamide, PBO (poly(p-phenylene benzobisoxazole), polyphenylene sulfide), polyester, acrylic, polyamide, polyolefin, polyvinyl alcohol, and polyarylate; natural fibers such as cellulose, pulp, cotton, wool, and silk; and regenerated fibers such as proteins, polypeptides, and alginic acid.
[0172] The content of the filler in 100% by mass of the composition is preferably 3 to 60% by mass.
[0173] The composition of the present invention is cured by active energy rays, so it is preferred to use a polymerization initiator, particularly a photopolymerization initiator. As the photopolymerization initiator, a known photopolymerization initiator can be used, for example, one or more selected from the group consisting of acetophenones, benzyl ketals, and benzophenones can be preferably used.
[0174] Specific examples of the photopolymerization initiator include 2,2-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxycyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-propane-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one, 2-benzyl-2-dimethylamino-1-phenylpropane-1-one, and the like. -(4-morpholinylphenyl)-butane-1-one, diethoxyacetophenone, oligomeric {2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone} and 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2-methyl-propane-1-one and other acetophenone compounds; benzophenone, 4-phenylbenzophenone, 2,4,6-trimethylbenzophenone and 4-benzoyl-4'-methyl-diphenyl sulfide Benzophenone compounds; α-ketoester compounds such as methyl benzoylformate, 2-(2-oxo-2-phenylacetoxyethoxy)ethyl oxyphenylacetic acid and 2-(2-hydroxyethoxy)ethyl oxyphenylacetic acid; phosphine oxide compounds such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide benzoin compounds such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether and benzoin isobutyl ether; titanocene compounds; acetophenone / benzophenone mixed photoinitiators such as 1-[4-(4-benzoylphenylsulfonyl)phenyl]-2-methyl-2-(4-methylphenylsulfinyl)propane-1-one; oxime ester photopolymerization initiators such as 2-(O-benzoyloxime)-1-[4-(phenylthio)]-1,2-octanedione; and camphorquinone, etc.
[0175] The photopolymerization initiator may be used alone or in combination of two or more thereof. The amount of the photopolymerization initiator used is preferably 1 to 15% by mass, more preferably 2 to 10% by mass, based on 100% by mass of the composition.
[0176] The composition of the present invention may also contain an ultraviolet absorber for the purpose of improving weather resistance. Various compounds or substances can be used as the ultraviolet absorber.
[0177] Specific examples of the ultraviolet absorber include: 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxy-phenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2-[4-[(2-hydroxy-3-tridecyloxypropyl)oxy]-2-hydroxy-phenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2-[4-[(2-hydroxy-3-(2 Benzotriazine-based ultraviolet absorbers such as 2-(2-hydroxy-4-[1-octyloxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine, 2,4-bis(2-hydroxy-4-butoxyphenyl)-6-(2,4-bis-butoxyphenyl)-1,3,5-triazine, and 2-(2-hydroxy-4-[1-octyloxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine;
[0178] Benzotriazole-based ultraviolet absorbers such as 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol, 2-(2-hydroxy-5-tert-butylphenyl)-2H-benzotriazole, and 2-[2-hydroxy-5-(2-(meth)acryloyloxyethyl)phenyl]-2H-benzotriazole; benzophenone-based ultraviolet absorbers such as 2,4-dihydroxybenzophenone and 2-hydroxy-4-methoxybenzophenone; cyanoacrylate-based ultraviolet absorbers such as ethyl-2-cyano-3,3-diphenylacrylate and octyl-2-cyano-3,3-diphenylacrylate; inorganic microparticles that absorb ultraviolet rays such as titanium oxide microparticles, zinc oxide microparticles, and tin oxide microparticles. The ultraviolet absorbers listed above may be used alone or in combination of two or more.
[0179] Commercially available ultraviolet absorbers may be used. Commercially available products include TINUVIN PS, TINUVIN 99-2, TINUVIN 234, TINUVIN 326, TINUVIN 329, TINUVIN 900, TINUVIN 928, TINUVIN 360, TINUVIN 384-2, TINUVIN 400, TINUVIN 405, TINUVIN 460, TINUVIN 477, and TINUVIN 479 (all manufactured by BASF); ADK STAB LA-46, ADK STAB LA-F70, ADK STAB LA-29, ADK STAB LA-31G, ADK STAB LA-32, and ADK STAB LA-36 (all manufactured by ADEKA CORPORATION); and RUVA-93 (manufactured by Otsuka Chemical Co., Ltd.).
[0180] From the viewpoint of improving weather resistance, benzotriazine-type ultraviolet absorbers or ultraviolet absorbers having a (meth)acryloyl group are preferred, and TINUVIN 400, TINUVIN 405, and TINUVIN 479 (all manufactured by BASF) are preferred, and ADK STAB LA-46 (manufactured by ADEKA CORPORATION) and RUVA-93 (manufactured by Otsuka Chemical Co., Ltd.) are preferred.
[0181] The amount of the ultraviolet absorber used is preferably 0.5 to 20% by mass, more preferably 1 to 10% by mass, based on 100% by mass of the composition.
[0182] The composition of the present invention may also contain a hindered amine light stabilizer (HALS) for the purpose of improving weather resistance.
[0183] As the hindered amine light stabilizer, a known hindered amine light stabilizer can be used, and specific examples thereof include bis(2,2,6,6-tetramethyl-4-piperidyl) sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate, bis(1-methoxy-2,2,6,6-tetramethyl-4-piperidyl) sebacate, bis(1-ethoxy-2,2,6,6-tetramethyl-4-piperidyl) sebacate, bis(1-propoxy-2,2,6,6-tetramethyl-4-piperidyl) sebacate, bis(1-butoxy-2,2,6,6-tetramethyl-4-piperidyl) sebacate, bis(1-pentyloxy-2,2,6,6-tetramethyl-4-piperidyl) sebacate, bis(1-hexyloxy-2,2,6,6-tetramethyl-4-piperidyl) sebacate, bis(1-heptyloxy-2,2,6,6-tetramethyl-4-piperidyl) sebacate, bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidyl) sebacate, bis(1-nonyloxy-2,2,6,6-tetramethyl bis(1-decyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis(1-dodecyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidinyl)-2-(4-methoxy-benzylidene) malonate, tetrakis(1,2,2,6,6-pentamethyl-4-piperidinyl) 1,2,3,4-butanetetracarboxylate, tetrakis(1,2,2,6,6-pentamethyl-4-piperidinyl) 1,2,3,4-butanetetracarboxylic acid ester, condensation product of 1,2,3,4-butanetetracarboxylic acid with 1,2,2,6,6-pentamethyl-4-piperidinol and β,β,β,β-tetramethyl-3,9-(2,4,8,10-tetraoxaspiro[5,5]undecane)diethanol, condensation product of 1,2,3,4-butanetetracarboxylic acid with 1,2,2,6,6-pentamethyl-4-piperidinol and β,β,β,β-tetramethyl-3,9-(2,4,8,10-tetraoxaspiro[5,5]undecane)diethanol, etc.
[0184] Commercially available hindered amine light stabilizers may be used. Commercially available products include TINUVIN 123, TINUVIN 292, TINUVIN 152, TINUVIN 144, TINUVIN 622SF), TINUVIN 111FDL, and TINUVIN 249 (all manufactured by BASF); and ADK STAB LA-52, ADK STAB LA-57, ADK STAB LA-63P, ADK STAB LA-68, ADK STAB LA-72, ADK STAB LA-81, ADK STAB LA-82, and ADK STAB LA-87 (all manufactured by ADEKA CORPORATION).
[0185] From the viewpoint of improving weather resistance, a hindered amine light stabilizer having no (meth)acryloyl group is preferred. TINUVIN 123, TINUVIN 152, and TINUVIN 144 (all manufactured by BASF) are preferred; ADK STAB LA-52, ADK STAB LA-57, ADK STAB LA-63P, ADK STAB LA-68, ADK STAB LA-72, and ADK STAB LA-81 (manufactured by ADEKA CORPORATION) are preferred. More preferred are TINUVIN 123 and TINUVIN 152 (all manufactured by BASF); ADK STAB LA-63P, ADK STAB LA-68, ADK STAB LA-72, and ADK STAB LA-81 (manufactured by ADEKA CORPORATION).
[0186] The amount of the hindered amine light stabilizer used is preferably 0.01 to 10% by mass, more preferably 0.1 to 5% by mass, based on 100% by mass of the composition.
[0187] Various surface modifiers may be added to the composition of the present invention for the purpose of improving leveling during coating, improving the smoothness of the cured film and improving scratch resistance, etc. As the surface modifier, various additives that modify the surface properties and are commercially available under the names of surface adjusters, leveling agents, smoothness imparting agents, antifouling imparting agents, etc. may be used. Among these, silicone-based surface modifiers and fluorine-based surface modifiers are suitable.
[0188] Specifically, silicone polymers and oligomers having silicone chains and polyalkylene oxide chains, silicone polymers and oligomers having silicone chains and polyester chains, fluorine polymers and oligomers having perfluoroalkyl and polyalkylene oxide chains, fluorine polymers and oligomers having perfluoroalkyl ether chains and polyalkylene oxide chains, etc. can be listed. One or more of them can be used. For the purpose of improving the lasting power of smoothness, substances containing (meth)acryloyl groups in the molecule can be used. Specific surface modifiers include: EBECRYL 350 (Daicel-Allnex Ltd.), BYK-333 (BYK-ChemieJapan), BYK-377 (BYK-Chemie Japan), BYK-378 (BYK-Chemie Japan), BYK-UV3500 (BYK-Chemie Japan), BYK-UV3505 (BYK-Chemie) Japan), BYK-UV3576 (BYK-Chemie Japan), MEGAFAC RS-75 (DIC Co., Ltd.), MEGAFAC RS-76-E (DIC Co., Ltd.), MEGAFAC RS-72-K (DIC Co., Ltd.), MEGAFAC RS-76-NS (DIC Co., Ltd.), MEGAFAC RS-90 (DIC Co., Ltd.), MEGAFAC RS-91 (DIC Co., Ltd.), MEGAFAC RS-55 (DIC Corporation), Optool DAC-HP (DAIKIN INDUSTRIES, LTD.,), ZX-058-A (T&K TOKA CORPORATION), ZX-201 (T&K TOKA CORPORATION), ZX-202 (T&K TOKA CORPORATION), ZX-212 (T&K TOKA CORPORATION), ZX-214-A (T&K TOKA CORPORATION), X-22-164AS (Shin-Etsu Chemical Co., Ltd.), X-22-164A (Shin-Etsu Chemical Co., Ltd.), X-22-164B (Shin-Etsu Chemical Co., Ltd.), X-22-164C (Shin-Etsu Chemical Co., Ltd.), X-22-164E (Shin-Etsu Chemical Co., Ltd.), X-22-174DX (Shin-Etsu Chemical Co., Ltd.), etc.
[0189] The active energy ray-curable covering composition of the present invention can be suitably used as a cured film for protecting a substrate by irradiating active energy rays after being applied to at least one side of various materials. The cured film comprising the composition of the present invention has weather resistance and abrasion resistance and high chemical resistance, and has excellent adhesion to various materials even in harsh environments such as high temperature and high humidity, so it exhibits excellent effects when used as a protective film for materials used for a long time in harsh environments such as outdoors and around automobiles.
[0190] <Molding products>
[0191] (Structure / Material)
[0192] The molded article of the present invention comprises a cured film of the active energy ray-curable covering composition of the present invention and a substrate.
[0193] The substrate is not particularly limited and can be appropriately selected according to the intended use. Examples thereof include plastic, wood, metal (steel, stainless steel, aluminum, etc.), metal oxides, paper, silicon or modified silicon, etc. It may also be a substrate obtained by joining different materials, or a substrate obtained by laminating the present composition or other compositions on a substrate in the form of a primer.
[0194] The shape of the substrate is not particularly limited, and can be any shape that matches the purpose, such as a flat plate, a sheet, or a three-dimensional shape with curvature (bend) on the entire surface or in part. In addition, the hardness and thickness of the substrate are also not limited.
[0195] The active energy ray-curable coating composition of the present invention has excellent adhesion to plastic substrates (resin substrates). As mentioned above, resin materials have low abrasion resistance and thus have disadvantages such as easy loss of gloss, poor transparency and weather resistance, and therefore these disadvantages can be improved by coating with the composition of the present invention.
[0196] As a plastic substrate, the resin is not particularly limited, for example, the aforementioned thermosetting resin or thermoplastic resin can be used. As a substrate, it can be a substrate obtained by mixing one or more resins alone, or it can be a substrate having a single layer or a laminated structure of more than two layers. In addition, these plastic substrates can be fiber reinforced (Fiber Reinforced Polymer, FRP).
[0197] When obtaining a transparent molded article, it is preferable to use a polycarbonate resin (for example, aliphatic polycarbonate, aromatic polycarbonate, alicyclic polycarbonate, etc.), polymethyl methacrylate resin, polystyrene resin, etc. as the plastic base material.
[0198] In addition, within the scope that does not hinder the effects of the present invention, the substrate may also contain known additives such as known antistatic agents, antifogging agents, anti-blocking agents, ultraviolet absorbers, antioxidants, pigments, organic fillers, inorganic fillers, light stabilizers, crystal nucleating agents, lubricants, etc.
[0199] The molded article of the present invention may further have a second substrate on the substrate and the cured film. The material of the second substrate is not particularly limited, and examples thereof include wood, metal, metal oxide, plastic, paper, silicon or modified silicon, and may be a substrate obtained by joining different materials. The shape of the substrate is not particularly limited, and may be any shape that meets the purpose, such as a flat plate, a sheet, or a three-dimensional shape with a curvature on the entire surface or a portion thereof. In addition, the hardness and thickness of the substrate are also not limited.
[0200] The molded product of the present invention has high adhesion to both plastics and inorganic substances, and therefore can also be preferably used as an interlayer material of different materials. It is particularly preferred that the substrate is plastic and the second substrate is an inorganic layer. As the inorganic layer, for example, quartz, sapphire, glass, optical film, ceramic material, inorganic oxide, vapor-deposited film (CVD, PVD, sputtering), magnetic film, reflective film, Ni, Cu, Cr, Fe, stainless steel and other metals, paper, SOG (spin-on glass, Spin On Glass), SOC (spin-on carbon, Spin On Carbon), polyester-polycarbonate-polyimide and other plastic layers, TFT array substrates, PDP electrode plates, ITO or metal and other conductive substrates, insulating substrates, silicon, silicon nitride, polycrystalline silicon, silicon oxide, amorphous silicon and other silicon-based substrates, etc. can be listed.
[0201] (Manufacturing method)
[0202] The molded article of the present invention is obtained by coating the surface of a substrate with the composition of the present invention.
[0203] The base material may be covered by directly applying the composition to the base material, directly molding the composition and curing it, or by laminating a cured product of the composition.
[0204] In the case of direct coating, the coating method is not particularly limited, and examples thereof include spraying, spin coating, dipping, roll coating, blade coating, doctor roll coating, doctor blade coating, curtain coating, slit coating, screen printing, and inkjet coating.
[0205] In the case of direct molding, there can be mentioned in-mold molding, insert molding, vacuum molding, extrusion lamination molding, press molding and the like.
[0206] When the cured product of the composition is laminated, a semi-cured cured product may be laminated on the substrate and then completely cured, or a completely cured product may be laminated on the substrate.
[0207] Since the composition of the present invention contains a compound having a polymerizable unsaturated group, it can be cured by irradiation with active energy rays.
[0208] Examples of active energy rays include ultraviolet rays, electron beams, ionizing radiation such as α rays, β rays, and γ rays. Among these, ultraviolet rays (UV) are particularly preferred from the viewpoint of curability and convenience.
[0209] Here, when ultraviolet rays are used as active energy rays, the device for irradiating the ultraviolet rays includes, for example, a low-pressure mercury lamp, a high-pressure mercury lamp, an ultrahigh-pressure mercury lamp, a metal halide lamp, an electrodeless lamp (melting lamp), a chemical lamp, a black light lamp, a mercury-xenon lamp, a short arc lamp, a helium-cadmium laser, an argon laser, sunlight, a light-emitting diode (LED) lamp, etc. By using these to irradiate the coated or molded composition with ultraviolet rays having a wavelength of about 180 to 400 nm, a cured film or a cured product can be obtained. The irradiation amount of ultraviolet rays can be appropriately selected according to the type and amount of the photopolymerization initiator used.
[0210] In addition, the molded product of the present invention is also excellent in processability after the active energy ray-curable covering composition is cured to become a cured film, so it can be bent together with the substrate. For example, after the coating substrate is directly coated with the covering composition for a flat substrate and the substrate after coating is obtained, even after the coating film is irradiated with active energy rays and made into a substrate with a cured film (that is, a molded product as a laminate), it can also be bent, so there is no need to worry about applying the covering composition to the curved substrate, which can significantly improve the productivity of the bending material. In addition, the molded product of the present invention is not only very excellent in bendability under heating, but also excellent in hard coating after hot bending.
[0211] When bending is performed, the thickness of the coating obtained by applying the composition of the present invention is preferably 0.5 to 40 μm, more preferably 3 to 35 μm, further preferably 5 to 30 μm, and particularly preferably 10 to 25 μm. By setting the thickness to be above the lower limit, wear resistance and weather resistance can be fully exerted, and by setting the thickness to be below the upper limit, bendability can be improved.
[0212] The bending method is not particularly limited, and examples thereof include bending methods in which the laminate is directly bent, and processing methods such as press molding, free blow molding, vacuum molding, pressure molding, and double composite molding.
[0213] The heat bending process is preferably performed at 80° C. or higher, more preferably at 150° C. or higher. The upper limit temperature can be appropriately set within a range lower than the melting temperature of the substrate.
[0214] (use)
[0215] The molded product of the present application is particularly suitable for various protective materials due to its excellent weather resistance, abrasion resistance, chemical resistance and adhesion. For example, it can be used for building materials, residential equipment, transportation aircraft such as automobiles / ships / aircrafts / railways, electronic materials, recording materials, optical materials, lighting, packaging materials, protection of outdoor installations, optical fiber covering, resin glass protection, etc., and in particular, it can be used in automobile headlight lenses, automobile glass windows, automobile body exteriors, building materials plastics, and building materials steel plates.
[0216] Example
[0217] Hereinafter, the present invention will be described in more detail using Examples and Comparative Examples, but the present invention is not limited to the following embodiments. In addition, in the present examples, "parts" and "%" are based on mass unless otherwise specified.
[0218] (Synthesis Example 1: Synthesis of UA-1)
[0219] In a 1-liter flask equipped with a stirrer, a gas introduction tube, a condenser, and a thermometer, "BURNOCK DN-902S" manufactured by DIC Corporation (NCO equivalent 23.5 wt%, 178.72 parts by mass), 2,6-di-tert-butyl-4-methylphenol (0.84 parts by mass), methoxyhydroquinone (0.084 parts by mass), and dibutyltin diacetate (0.084 parts by mass) were added, and the temperature was raised to 70°C. 2-Hydroxyethyl acrylate (77.4 parts by mass) and "PTMG-1000" manufactured by Mitsubishi Chemical Group Corporation (hydroxyl value: 113.95, 164.11 parts by mass) were added in batches over 1 hour. After the addition, the reaction was carried out at 80°C until the 2250 cm-1 isocyanate group was -1 The reaction mixture was stirred for 2 hours until the infrared absorption spectrum of disappeared, thereby obtaining urethane resin UA-1 having a (meth)acryloyl group.
[0220] (Synthesis Example 2: Synthesis of UA-2)
[0221] In a 1-liter flask equipped with a stirrer, a gas introduction tube, a condenser, and a thermometer, "BURNOCK DN-902S" manufactured by DIC Corporation (NCO equivalent 23.5 wt%, 178.72 parts by mass), 2,6-di-tert-butyl-4-methylphenol (0.84 parts by mass), methoxyhydroquinone (0.084 parts by mass), and dibutyltin diacetate (0.084 parts by mass) were added, and the temperature was raised to 70°C. 2-Hydroxyethyl acrylate (77.4 parts by mass) and "PLACCEL210" manufactured by Daicel Corporation (hydroxyl value: 113.4, 164.90 parts by mass) were added in batches over 1 hour. After the addition, the reaction was carried out at 80°C until the 2250 cm-1 isocyanate group was -1 The reaction mixture was stirred for 2 hours until the infrared absorption spectrum of disappeared, thereby obtaining urethane resin UA-2 having a (meth)acryloyl group.
[0222] (Synthesis Example 3: Synthesis of UA-3)
[0223] In a 1-liter flask equipped with a stirrer, a gas introduction tube, a condenser, and a thermometer, "BURNOCK DN-902S" manufactured by DIC Corporation (NCO equivalent 23.5 wt%, 178.72 parts by mass), 2,6-di-tert-butyl-4-methylphenol (1.05 parts by mass), methoxyhydroquinone (0.11 parts by mass), and dibutyltin diacetate (0.11 parts by mass) were added, and the temperature was raised to 70°C, and PLACCEL FA-2D (344.0 parts by mass) was added in batches over 1 hour. After the addition, the reaction was carried out at 80°C until the 2250 cm-1 isocyanate group was -1 The reaction mixture was stirred for 2 hours until the infrared absorption spectrum of disappeared, thereby obtaining urethane resin UA-3 having a (meth)acryloyl group.
[0224] (Synthesis Example 4: Synthesis of UA-4)
[0225] In a 1-liter flask equipped with a stirrer, a gas introduction tube, a condenser, and a thermometer, "Basonat (registered trademark) HA3000" manufactured by BASF (NCO equivalent 19.5 wt%, 213.39 parts by mass), 2,6-di-tert-butyl-4-methylphenol (0.91 parts by mass), methoxyhydroquinone (0.09 parts by mass), and dibutyltin diacetate (0.09 parts by mass) were added, and the temperature was raised to 70° C., and 2-hydroxyethyl acrylate (77.4 parts by mass) and "PTMG-1000" manufactured by Mitsubishi Chemical Group Corporation (hydroxyl value: 113.95, 164.11 parts by mass) were added in batches over 1 hour. After the addition, the reaction was carried out at 80° C. until 2250 cm-1 representing an isocyanate group was reached. -1The reaction mixture was stirred for 2 hours until the infrared absorption spectrum of disappeared, thereby obtaining urethane resin UA-4 having a (meth)acryloyl group.
[0226] (Synthesis Example 5: Synthesis of UA-5)
[0227] In a 1-liter flask equipped with a stirrer, a gas introduction tube, a condenser, and a thermometer, "Basonat (registered trademark) HA 3000" manufactured by BASF (NCO equivalent 19.5 wt%, 213.39 parts by mass), 2,6-di-tert-butyl-4-methylphenol (0.91 parts by mass), methoxyhydroquinone (0.09 parts by mass), and dibutyltin diacetate (0.09 parts by mass) were added, and the temperature was raised to 70° C., and 2-hydroxyethyl acrylate (77.4 parts by mass) and "PLACCEL 210" manufactured by Daicel Corporation (hydroxyl value: 113.4, 164.90 parts by mass) were added in batches over 1 hour. After the addition, the reaction was carried out at 80° C. until 2250 cm-1 representing an isocyanate group was obtained. -1 The reaction mixture was stirred for 2 hours until the infrared absorption spectrum of disappeared, thereby obtaining urethane resin UA-5 having a (meth)acryloyl group.
[0228] (Synthesis Example 6: Synthesis of UA-6)
[0229] In a 1-liter flask equipped with a stirrer, a gas introduction tube, a condenser, and a thermometer, "Basonat (registered trademark) HA3000" manufactured by BASF (NCO equivalent 19.5 wt%, 213.39 parts by mass), 2,6-di-tert-butyl-4-methylphenol (1.12 parts by mass), methoxyhydroquinone (0.11 parts by mass), and dibutyltin diacetate (0.11 parts by mass) were added, and the temperature was raised to 70°C, and PLACCEL FA-2D (344.0 parts by mass) was added in batches over 1 hour. After the addition, the reaction was carried out at 80°C until the 2250 cm-1 isocyanate group. -1 The reaction mixture was stirred for 2 hours until the infrared absorption spectrum of disappeared, thereby obtaining urethane resin UA-6 having a (meth)acryloyl group.
[0230] (Synthesis Example 7: Synthesis of UA-7)
[0231] In a 1-liter flask equipped with a stirrer, a gas introduction tube, a condenser, and a thermometer, "BURNOCK DN-902S" manufactured by DIC Corporation (NCO equivalent 23.5 wt%, 178.72 parts by mass), 2,6-di-tert-butyl-4-methylphenol (0.59 parts by mass), methoxyhydroquinone (0.06 parts by mass), and dibutyltin diacetate (0.06 parts by mass) were added, and the temperature was raised to 70°C, and 2-hydroxyethyl acrylate (116.2 parts by mass) was added in portions over 1 hour. After the addition, the reaction was carried out at 80°C until the 2250 cm-1 isocyanate group was -1 The reaction mixture was stirred for 2 hours until the infrared absorption spectrum of disappeared, thereby obtaining urethane resin UA-7 having a (meth)acryloyl group.
[0232] (Synthesis Example 8: Synthesis of UA-8)
[0233] In a 1-liter flask equipped with a stirrer, a gas introduction tube, a condenser, and a thermometer, "BURNOCK DN-902S" manufactured by DIC Corporation (NCO equivalent 23.5 wt%, 178.72 parts by mass), 2,6-di-tert-butyl-4-methylphenol (0.51 parts by mass), methoxyhydroquinone (0.05 parts by mass), and dibutyltin diacetate (0.05 parts by mass) were added, and the temperature was raised to 70°C. 2-Hydroxyethyl acrylate (77.4 parts by mass) and "MPD (3-methyl-1,5-pentanediol)" manufactured by KURARAY CO., LTD. (19.70 parts by mass) were added in batches over 1 hour. After the addition, the reaction was carried out at 80°C until the 2250 cm-1 concentration representing the isocyanate group was 1.5 wt%. -1 The reaction mixture was stirred for 2 hours until the infrared absorption spectrum of disappeared, thereby obtaining urethane resin UA-8 having a (meth)acryloyl group.
[0234] (Synthesis Example 9: Synthesis of UA-9)
[0235] In a 1-liter flask equipped with a stirrer, a gas introduction tube, a condenser, and a thermometer, "BURNOCK DN-902S" manufactured by DIC Corporation (NCO equivalent 23.5 wt%, 178.72 parts by mass), 2,6-di-tert-butyl-4-methylphenol (0.65 parts by mass), methoxyhydroquinone (0.07 parts by mass), and dibutyltin diacetate (0.07 parts by mass) were added, and the temperature was raised to 70°C, and 4-hydroxybutyl acrylate (144.2 parts by mass) was added in portions over 1 hour. After the addition, the reaction was carried out at 80°C until the 2250 cm-1 isocyanate group was -1 The reaction mixture was stirred for 2 hours until the infrared absorption spectrum of disappeared, thereby obtaining urethane resin UA-9 having a (meth)acryloyl group.
[0236] (Synthesis Example 10: Synthesis of UA-10)
[0237] In a 1-liter flask equipped with a stirrer, a gas introduction tube, a condenser, and a thermometer, "Basonat (registered trademark) HA3000" manufactured by BASF (NCO equivalent 19.5 wt%, 213.39 parts by mass), 2,6-di-tert-butyl-4-methylphenol (0.66 parts by mass), methoxyhydroquinone (0.07 parts by mass), and dibutyltin diacetate (0.07 parts by mass) were added, and the temperature was raised to 70°C, and 2-hydroxyethyl acrylate (116.2 parts by mass) was added in batches over 1 hour. After the addition, the reaction was carried out at 80°C until the 2250 cm-1 isocyanate group. -1 The reaction mixture was stirred for 2 hours until the infrared absorption spectrum of disappeared, thereby obtaining urethane resin UA-10 having a (meth)acryloyl group.
[0238] (Synthesis Example 11: Synthesis of UA-11)
[0239] In a 1-liter flask equipped with a stirrer, a gas introduction tube, a condenser, and a thermometer, "Basonat (registered trademark) HA3000" manufactured by BASF (NCO equivalent 19.5 wt%, 213.39 parts by mass), 2,6-di-tert-butyl-4-methylphenol (0.72 parts by mass), methoxyhydroquinone (0.07 parts by mass), and dibutyltin diacetate (0.07 parts by mass) were added, and the temperature was raised to 70°C. 4-Hydroxybutyl acrylate (144.2 parts by mass) was added in batches over 1 hour. After the addition, the reaction was carried out at 80°C until the 2250 cm-1 isocyanate group. -1 The reaction mixture was stirred for 2 hours until the infrared absorption spectrum of disappeared, thereby obtaining urethane resin UA-11 having a (meth)acryloyl group.
[0240] (Synthesis Example 12: UA-12)
[0241] In a 1-liter flask equipped with a stirrer, a gas introduction tube, a condenser, and a thermometer, "Desmodur I" manufactured by Coverstro (111.15 parts by mass), 2,6-di-tert-butyl-4-methylphenol (0.94 parts by mass), methoxyhydroquinone (0.09 parts by mass), and dibutyltin diacetate (0.09 parts by mass) were added, and the temperature was raised to 70°C. "Aronix M-306 (hydroxyl value 157.2)" manufactured by Toagosei Co., Ltd. (356.87 parts by mass) was added in batches over 1 hour. After the addition, the reaction was carried out at 80°C until the 2250 cm-1 isocyanate group was -1 The reaction mixture was stirred for 2 hours until the infrared absorption spectrum of disappeared, thereby obtaining urethane resin UA-12 having a (meth)acryloyl group represented by general formula (3).
[0242] (Synthesis Example 13: UA-13)
[0243] In a 1-liter flask equipped with a stirrer, a gas introduction tube, a condenser, and a thermometer, "Desmodur H" (84.10 parts by mass) manufactured by Coverstro, 2,6-di-tert-butyl-4-methylphenol (1.39 parts by mass), methoxyhydroquinone (0.14 parts by mass), and dibutyltin diacetate (0.14 parts by mass) were added, and the temperature was raised to 70°C. "Aronix M-403 (hydroxyl value 92)" (609.78 parts by mass) manufactured by Toagosei Co., Ltd. was added in batches over 1 hour. After the addition, the reaction was carried out at 80°C until the 2250 cm-1 concentration representing the isocyanate group was 0.1%. -1 The infrared absorption spectrum of disappears, thereby obtaining UA-13 having a (meth)acryloyl group represented by the general formula (3).
[0244] (Synthesis Example 14: UA-14)
[0245] In a 1-liter flask equipped with a stirrer, a gas introduction tube, a condenser, and a thermometer, "Desmodur I" manufactured by Coverstro (111.15 parts by mass), 2,6-di-tert-butyl-4-methylphenol (1.44 parts by mass), methoxyhydroquinone (0.14 parts by mass), and dibutyltin diacetate (0.14 parts by mass) were added, and the temperature was raised to 70°C. "Aronix M-403 (hydroxyl value 92)" manufactured by Toagosei Co., Ltd. (609.78 parts by mass) was added in batches over 1 hour. After the addition, the reaction was carried out at 80°C until the 2250 cm-1 isocyanate group. -1 The infrared absorption spectrum of disappears, thereby obtaining UA-14 having a (meth)acryloyl group represented by the general formula (3).
[0246] (Synthesis Example 15: UA-15)
[0247] In a 1-liter flask equipped with a stirrer, a gas introduction tube, a condenser, and a thermometer, "BURNOCK DN-902S" (178.72 parts by mass) manufactured by DIC Corporation, 2,6-di-tert-butyl-4-methylphenol (1.01 parts by mass), methoxyhydroquinone (0.10 parts by mass), and dibutyltin diacetate (0.10 parts by mass) were added, and the temperature was raised to 70°C. "Aronix M-306 (hydroxyl value 157.2)" (356.87 parts by mass) manufactured by Toagosei Co., Ltd. was added in batches over 1 hour. After the addition, the reaction was carried out at 80°C until 2250 cm-1 of isocyanate group was obtained. -1 The reaction mixture was stirred for 2 hours until the infrared absorption spectrum of disappeared, thereby obtaining urethane resin UA-15 having a (meth)acryloyl group represented by general formula (3).
[0248] (Synthesis Example 16: UA-16)
[0249] In a 1-liter flask equipped with a stirrer, a gas introduction tube, a condenser, and a thermometer, "BURNOCK DN-902S" (178.72 parts by mass) manufactured by DIC Corporation, 2,6-di-tert-butyl-4-methylphenol (1.57 parts by mass), methoxyhydroquinone (0.16 parts by mass), and dibutyltin diacetate (0.16 parts by mass) were added, and the temperature was raised to 70°C. "Aronix M-403 (hydroxyl value 92)" (203.26 parts by mass) manufactured by Toagosei Co., Ltd. was added in batches over 1 hour. After the addition, the reaction was carried out at 80°C until 2250 cm-1 of isocyanate group was obtained. -1 The infrared absorption spectrum of disappears, thereby obtaining UA-16 having a (meth)acryloyl group represented by the general formula (3).
[0250] (Example 1)
[0251] 1 part by mass of 2-hydroxyethyl isocyanurate triacrylate as the component (A), 90 parts by mass of UA-4 as the component (B-1), 8 parts by mass of UA-10 as the component (B-2), 1 part by mass of UA-12 as the component (C), 3 parts by mass of Omnirad 819 (manufactured by IGM) as a photoinitiator, 0.5 parts by mass of TINUVIN 123 as a HALS, 4 parts by mass of TINUVIN 479 as a UV absorber, and propylene glycol monomethyl ether as an organic solvent were uniformly mixed so that the solid content became 50% by mass, thereby preparing an active energy ray-curable coating composition of Example 1.
[0252] (Examples 2 to 46, Comparative Examples 1 to 4)
[0253] Except having changed into the composition shown in Tables 1-7, it carried out similarly to Example 1, and obtained the active energy ray-curable coating composition of each example.
[0254] [Preparation of evaluation samples]
[0255] The active energy ray-curable coating composition of each example was applied to a polycarbonate substrate (“Panlite L-1225ZL” manufactured by Teijin Limited) having a thickness of 3 mm using a bar coater, dried at 80° C. for 4 minutes, and then irradiated with an ultraviolet irradiation device (manufactured by GS-YUASA, high-pressure mercury lamp) at an illumination of 200 mW·cm 2 、Irradiation light quantity 1000mJ / m 2 The irradiation was performed to obtain a polycarbonate laminate having a cured film with a film thickness of 20 μm.
[0256] [Evaluation of chemical resistance]
[0257] For the evaluation sample of each example, a spot test was carried out using a 40 wt % sulfuric acid aqueous solution by a method in accordance with JIS K 5600-6 and a spot test by a drop method.
[0258] The maximum time during which no defective appearance of the coating film was confirmed was used as the evaluation result. 15 minutes or more was recorded as passing, and when no defective appearance was confirmed for more than 60 minutes, it was recorded as "60". The result time (unit: minutes) was recorded as "chemical resistance" in Tables 1 to 7.
[0259] [Abrasion resistance evaluation]
[0260] The cured film surface of each evaluation sample was rubbed according to ANSI 2007 (abrasion wheel CS-10F, 500 g, 500 times) to perform a Taber abrasion test. The abrasion resistance was evaluated by measuring the difference in haze between the initial state and after the Taber abrasion test, i.e., the haze value change ΔHaze (%).
[0261] The change in haze value before and after the test was calculated from the haze value obtained by measuring the transmittance value using a haze meter and using the following formula.
[0262] Th=Td / Tt×100
[0263] (Th: haze value (%), Td: scattered light transmittance, Tt: total light transmittance)
[0264] Regarding ΔHaze, a value of less than 20 was regarded as acceptable. ΔHaze is described in Tables 1 to 7 as “wear resistance”.
[0265] [Weather resistance evaluation A]
[0266] An accelerated weather resistance test (SUV test) was performed on the evaluation sample of each example under the following conditions.
[0267] Conditions: Repeated irradiation (63°C / 70%RH / 4 hours) → darkness (70°C / 90%RH / 4 hours) → condensation (30°C / 98%RH / 4 hours), with spraying before and after irradiation
[0268] The maximum time during which no cracks were observed on the cured film was used as the evaluation result, and 650 hours or more was recorded as acceptable. It should be noted that when no cracks were observed after more than 1296 hours, it was recorded as "1296". The results (unit: hours) were recorded as "Weather Resistance A" in Tables 1 to 7.
[0269] [Weather resistance evaluation B]
[0270] The SUV test was performed under the same conditions as those in the weather resistance evaluation A. The glass ribbon adhesion test was performed on the sample surface every 12 hours until 1296 hours. Thereafter, the surface state was observed and evaluated.
[0271] For the evaluation of the glass ribbon adhesion test, the surface state after the peeling test was observed. If peeling was observed, the time elapsed from that time was used as the evaluation result, and 650 hours or more was recorded as passing. It should be noted that if peeling was not observed after 1296 hours, it was recorded as "1296". The results (unit: hours) are recorded as "Weather Resistance B" in Tables 1 to 7.
[0272] [Table 1]
[0273]
[0274] [Table 2]
[0275]
[0276] [Table 3]
[0277]
[0278] [Table 4]
[0279]
[0280] [Table 5]
[0281]
[0282] [Table 6]
[0283]
[0284] [Table 7]
[0285]
[0286] The abbreviations shown in Tables 1 to 7 represent the following compounds or the compounds obtained in the above-mentioned synthesis examples, respectively.
[0287] A-1: 2-Hydroxyethyl isocyanurate triacrylate
[0288] UA-1 to UA-16: Compounds obtained in Synthesis Examples 1 to 16
[0289] DPHA: dipentaerythritol hexaacrylate (KAYARAD DPHA manufactured by Nippon Kayaku Co., Ltd.)
[0290] S-1: Modified silica fine particles ("MEK-AC2140Z" manufactured by Nissan Chemical Industries, Ltd.)
[0291] I-1: Photoinitiator "Omnirad 819" (trade name, manufactured by IGM)
[0292] H-1: Non-reactive HALS "TINUVIN 123" (trade name, manufactured by BASF)
[0293] H-2: Non-reactive HALS "TINUVIN 152" (trade name, manufactured by BASF)
[0294] H-3: Reactive HALS "ADK STAB LA-82" (trade name, manufactured by ADEKA CORPORATION)
[0295] UVA1: Triazine type ultraviolet absorber "TINUVIN 400" (trade name, manufactured by BASF)
[0296] UVA2: Triazine-type ultraviolet absorber "ADK STAB LA-46" (trade name, manufactured by ADEKA CORPORATION)
[0297] UVA3: Triazine type ultraviolet absorber "TINUVIN 479" (trade name, manufactured by BASF)
[0298] UVA4: Reactive ultraviolet absorber "RUVA-93" (trade name, manufactured by Otsuka Chemical Co., Ltd.)
[0299] From the results of Examples 1 to 46, it was confirmed that the cured film of the active energy ray-curable covering composition of the present invention was excellent in chemical resistance, abrasion resistance, weather resistance, and adhesion.
[0300] On the other hand, it was confirmed that: Comparative Example 1 not containing component (C) had poor chemical resistance; Comparative Examples 2 or 4 not containing component (A) had poor abrasion resistance or weather resistance; and Comparative Example 3 not containing component (B) had poor chemical resistance and weather resistance.
[0301] (Examples 47 to 60, Comparative Examples 5 to 7)
[0302] [Production of evaluation samples and bending test]
[0303] The active energy ray-curable coating composition of Example 2 was applied to a 2 mm thick polycarbonate substrate ("CARBOGLASS polish clear" manufactured by Asahi Glass Co., Ltd.) using a bar coater, dried at 80°C for 4 minutes, and then irradiated with an ultraviolet irradiation device (GS-YUASA, high pressure mercury lamp) at an illumination of 200 mW·cm 2 、Irradiation light quantity 1000mJ / m2 The irradiation was performed to obtain a bending laminate of Example 47 having a cured coating with a film thickness of 20 μm. The bending laminates of Examples 48 to 60 and Comparative Examples 5 to 7 were obtained in the same manner as in Example 47 except that the active energy ray-curable coating compositions of Examples or Comparative Examples shown as “Compositions” in Tables 8 to 10 were used instead of the active energy ray-curable coating composition of Example 2.
[0304] [Appearance evaluation]
[0305] After heating the bending laminate of each example at 170°C for 5 minutes in a thermostat, the cured film was rated as acceptable if wrinkles were not observed, and unacceptable if wrinkles were observed. The results are shown in Tables 8 to 10 as "Appearance".
[0306] [Adhesion Evaluation]
[0307] After heating the bending laminate of each example at 170°C for 5 minutes using a constant temperature machine, the bending laminate was wound around the outer circumference of a cylinder with a diameter of 10.5 to 3 cm with the cured film set on the outside to evaluate the bendability (bending property). The laminate that did not peel off at the maximum diameter where cracks were not confirmed on the cured film was recorded as qualified (○), and the laminate that peeled off was recorded as unqualified (×). The results are recorded in Tables 8 to 10 as "Adhesion".
[0308] [Evaluation of heat resistance bending properties]
[0309] After heating the bending laminate of each example at 170°C for 5 minutes using a constant temperature machine, the bending laminate was wound around the outer circumference of a cylinder with a diameter of 10.5 to 3 cm with the cured film set on the outside to evaluate the bendability (bending property). The maximum diameter at which no cracks were confirmed on the cured film was used as the evaluation result, and 10 cm or less was recorded as qualified. The results (unit: cm) are recorded in Tables 8 to 10 as "bending resistance".
[0310] [Table 8]
[0311]
[0312] [Table 9]
[0313]
[0314] [Table 10]
[0315]
[0316] The above results confirm that the cured films of the active energy ray-curable covering compositions of the present invention of Examples 47 to 60 are excellent in bending workability. On the other hand, it is confirmed that the cured films of Comparative Examples 5 to 7 are inferior in appearance, adhesion, and bending resistance.
Claims
1. An active energy ray-curable coating composition, characterized in that: Contains the following components (A) to (C), wherein: Contains a compound represented by the following formula (1) as component (A), Contains a compound represented by the following formula (2) as component (B), The compound having 6 or more (meth)acryloyl groups in one molecule is contained as the component (C), In the formula, R 1 , R 2 and R 3 Each independently represents an oxyalkylene group or a polyoxyalkylene group, X 1 , X 2 and X 3 Each independently represents CH2=CR 4 -CO-, CH2=CR 4 -CO(O(CH2)5-CO) a1 -, a hydrogen atom or an alkyl group, R 4 Represents a hydrogen atom or a methyl group, multiple R 4 are optionally the same or different, a1 is an integer greater than 1, wherein X 1 ~X 3 At least 2 of them are CH2=CR 4 -CO- or CH2=CR 4 -CO(O(CH2)5-CO) a1 -, In the formula, R 21 ~R 25 each independently represents a group having a polymerizable group, Z 21 ~Z 23 Each independently represents a group represented by the following formula (2z), L 21 ~L 22 Each independently represents a divalent linking group, n1 to n2 are each independently 0 or 1, In the formula, X 21 represents an alkylene group having 2 to 17 carbon atoms, * is the connection key, Z 1 represents an oxygen atom or a nitrogen atom, Z 2 represents a hydrogen atom or -C(=O)-, wherein Z 1 When Z is an oxygen atom, 2 is a hydrogen atom. On the other hand, Z 1 When Z is a nitrogen atom, 2 is -C(=O)-, Z 1 The nitrogen atom and Z 2 The -C(=O)- of Formula (2z) is Z in the formula (2) 21 When the connecting bond * shown in B1 is connected to R 21 Bonding, the connecting bond shown in B2 and L 21 or R 22 Bonding, the connecting bond shown in B3 and L 22 or R 23 Bonding; Formula (2z) is Z in the formula (2) 22 When the connecting key * shown in B1 is connected to L 22 Bonding, the connecting bond shown in B2 and R 24 Bonding, the connecting bond shown in B3 and R 23 Bonding; Formula (2z) is Z in the formula (2) 23 When the connecting key * shown in B1 is connected to L 21 Bonding, the connecting bond shown in B2 and R 22 Bonding, the connecting bond shown in B3 and R 25 Bonding.
2. The active energy ray-curable coating composition according to claim 1, wherein The compound represented by the formula (2) is any of the compounds represented by the following formulae (2-1) to (2-4), In the formula, R 26 each independently represents a hydrogen atom or a methyl group, R 27 Each independently represents an alkylene group, R A -(O-CO-(CH2)5) n - or R A -(O-(CH2)4) n -, R A represents an alkylene group, n each independently represents an integer of 1 to 10, X 22 Each independently represents an alkylene group having 2 to 17 carbon atoms, and the plurality of R 26 , R 27 , X 22 are optionally the same as or different from each other, In the formula, R 26 , R 27 , X 22 Same as above, A1 represents a structure obtained by removing a hydroxyl group from the terminal of any of alkylene glycol, caprolactone-modified glycol, or polytetramethylene glycol, wherein the plurality of R 26 , R 27 , X 22 , A1 are optionally the same or different from each other, In the formula, R 26 , R 27 , X 22 As above, the multiple R 26 , R 27 , X 22 are optionally the same as or different from each other, In the formula, R 26 , R 27 , X 22 , A1 is the same as above, and the multiple R 26 , R 27 , X 22 They are optionally the same as or different from each other.
3. The active energy ray-curable coating composition according to claim 1, wherein In the total solid content of the components (A) to (C), the content of the component (A) is 1% by mass to 85% by mass, the content of the component (B) is 14% by mass to 98% by mass, and the content of the component (C) is 1% by mass to 20% by mass.
4. The active energy ray-curable coating composition according to claim 1, wherein The component (C) is a polyfunctional urethane acrylate obtained by reacting a diisocyanate compound or a triisocyanate compound with a compound represented by the following formula (3-1) or (3-2). In the formula, R 31 ~R 32 Each independently represents a hydrogen atom or a methyl group, and the multiple R 31 , R 32 They are optionally the same as or different from each other.
5. The active energy ray-curable coating composition according to claim 4, wherein The component (C) is a polyfunctional urethane acrylate obtained by reacting an isocyanate compound represented by the following formula (3-3) or (3-4) with a compound represented by the above formula (3-1) or (3-2), In the formula, X 31 ~X 32 Each independently represents an alkylene group having 2 to 17 carbon atoms, and R 33 Indicates -R C -O-CO-CH=CH2 or a structure obtained by removing a hydroxyl group from the compound represented by the formula (3-1) or (3-2), R C represents an alkylene group; multiple X in the formula 31 , X 32 They are optionally the same as or different from each other.
6. The active energy ray-curable coating composition according to claim 2, wherein The component (B) includes the component (B-1) and the component (B-2), The component (B-1) comprises: R in the formula (2-1) or (2-3) 27 At least one of the A -(O-CO-(CH2)5) n - or R A -(O-(CH2)4) n -, or A1 in the formula (2-2) or (2-4) is a compound having a structure obtained by removing a hydroxyl group from a terminal of polytetramethylene glycol or polycaprolactone diol, The component (B-2) comprises: R in the formula (2-1) or (2-3) 27 A compound which is an alkylene group, or a compound in which A1 in the formula (2-2) or (2-4) has a structure obtained by removing a hydroxyl group from the terminal of an alkylene glycol, In the total solid content of the components (A) to (C), the content of the component (B-1) is 9 mass % to 90 mass %, and the content of the component (B-2) is 5 mass % to 60 mass %.
7. The active energy ray-curable coating composition according to claim 1, wherein The active energy ray-curable coating composition contains no organic solvent or contains 30% by mass or less of an organic solvent based on the total amount of the composition. 8 . A molded article comprising a cured film of the active energy ray-curable covering composition according to claim 1 and a substrate.
9. The molded article according to claim 8, wherein The substrate is polycarbonate resin.
10. The molded article according to claim 8, which is used for automobile headlamp lenses, automobile glass windows, automobile body exteriors, plastics for building materials, and steel sheets for building materials.
11. A molded product obtained by bending the molded product according to claim 9 by heat bending.
Citation Information
Patent Citations
Method for obtaining antimicrobial and antifungal drug
UA130243C2
Active energy ray-curable coating composition, and molded article having cured film of the composition
CN101437904A
Hydroxyl-containing polyurethane resin, polyurethane resin and urethane (meth)acrylate resin using hydroxyl-containing polyurethane resin as starting material, production methods for these resins, overcoat composition, and uv-curable resin composition
CN107148435A
Active energy ray-curable coating composition, and molded article having cured film of the composition
JP2007314770A
Active energy ray-curable composition and molded article having cured coating film of the same
JP2010111810A